2017
DOI: 10.1038/bjc.2017.216
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 expression levels are elevated in pancreatic intraepithelial neoplasia cells in the Ptf1a-Cre; LSL-KrasG12D transgenic mouse model of pancreatic cancer

Abstract: Background:Pancreatic cancer is currently the third leading cause of cancer deaths in the United States and it is predicted to become the second by the year 2030. High-mobility group A1 protein (HMGA1) is an oncogenic transcription factor, localised and active in cell nuclei, that is linked to tumour progression in many human cancers, including pancreatic cancer. Overexpression of HMGA1 renders cancer cells resistant to chemotherapy. Although the Ptf1a-Cre; LSL-KrasG12D transgenic mouse is perhaps the most wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this study, NMR based metabonomics has been used to explore the potential of metabolic profiling for identification of potential biomarkers for detection of precancerous pancreatic intraepithelial neoplasia (PanIN) that precede pancreatic cancer [ 4 , 31 33 ]. The transgenic Ptf1a-Cre; LSL-KrasG12D mouse model used in this study has been extensively characterized and shown to display extensive PanIN that eventually progress to PDAC [ 4 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, NMR based metabonomics has been used to explore the potential of metabolic profiling for identification of potential biomarkers for detection of precancerous pancreatic intraepithelial neoplasia (PanIN) that precede pancreatic cancer [ 4 , 31 33 ]. The transgenic Ptf1a-Cre; LSL-KrasG12D mouse model used in this study has been extensively characterized and shown to display extensive PanIN that eventually progress to PDAC [ 4 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, NMR based metabonomics has been used to explore the potential of metabolic profiling for identification of potential biomarkers for detection of precancerous pancreatic intraepithelial neoplasia (PanIN) that precede pancreatic cancer [ 4 , 31 33 ]. The transgenic Ptf1a-Cre; LSL-KrasG12D mouse model used in this study has been extensively characterized and shown to display extensive PanIN that eventually progress to PDAC [ 4 , 31 33 ]. The Ptf1a-Cre; LSL-KrasG12D mouse model of pancreatic cancer is considered to recapitulate important characteristics of human pancreatic cancer, including spontaneous pancreatic tumor formation that is preceded by a precancerous PanIN stage [ 4 , 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All dissections and intestinal histologies were performed as described previously 22–29. Details regarding the histological procedures can be found in online supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer. Treatment outcomes for PDAC are generally poor due to the existence of distant tumor metastasis in 80–90% of patients at the time of diagnosis, since metastasis is a contraindication for surgical resection (3). Therefore, early tumor detection is crucial.…”
Section: Introductionmentioning
confidence: 99%